Iklim Organisasi dengan Organizatonal Citizenship Behavior pada Karyawan Bank X Padang - Harri Kurniawan (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2021)
The purpose of this study was to find out whether there is a relationship between Organizational Climate and Organizational Citizenship Behavior (OCB) at Bank X Padang. The independent variable in this study is organizational climate and the dependent variable is organizational citizenship behavior (OCB). The measuring instrument used in this study is the organizational climate scale and organizational citizenship behavior (OCB) scale. The sampling technique in this study used a saturated sampling technique. The sample in this study were all 56 employees of Bank X Padang. Test the validity and reliability in this study using the Alpha Cronbach technique. The results of the validity coefficient on the organizational climate move from rix=0.320 to rix=0.773 with a reliability coefficient of =0.911, while the organizational citizenship behavior (OCB) scale moves from rix=0.352 to rix=0.791 with a reliability coefficient of =0.944. Based on data analysis, obtained a correlation value of 0.455 with a significance level of 0.000 which means the hypothesis is accepted. This shows that there is a relationship between organizational climate and organizational citizenship behavior (OCB) at Bank X Padang. The effective contribution of the organizational climate variable to organizational citizenship behavior (OCB) is 21%. This can be interpreted that the organizational climate is able to make a positive contribution to organizational citizenship behavior (OCB)